Neuropeptide Y Attenuates Stress‐Induced Bone Loss Through Suppression of Noradrenaline Circuits. (October 2014) - Baldock, PA; Lin, S; Zhang, L; Karl, T; Shi, Y; Driessler, F; Zengin, A; Hörmer, B; Lee, NJ; Wong, IPL; Lin, EJD; Enriquez, RF; et al.
ABSTRACT Chronic stress and depression have adverse consequences on many organ systems, including the skeleton, but the mechanisms underlying stress‐induced bone loss remain unclear. Here we demonstrate that neuropeptide Y (NPY), centrally and peripherally, plays a critical role in protecting against stress‐induced bone loss. Mice lacking the anxiolytic factor NPY exhibit more anxious behavior and elevated corticosterone levels. Additionally, following a 6‐week restraint, or cold‐stress protocol, Npy‐null mice exhibit three‐fold greater bone loss compared to wild‐type mice, owing to suppression of osteoblast activity. This stress‐protective NPY pathway acts specifically through Y2 receptors. Centrally, Y2 receptors suppress corticotropin‐releasing factor expression and inhibit activation of noradrenergic neurons in the paraventricular nucleus. In the periphery, they act to control noradrenaline release from sympathetic neurons. Specific deletion of arcuate Y2 receptors recapitulates the Npy‐null stress response, coincident with elevated serum noradrenaline. Importantly, specific reintroduction of NPY solely in noradrenergic neurons of otherwise Npy‐null mice blocks the increase in circulating noradrenaline and the stress‐induced bone loss. Thus, NPY protects against excessive stress‐induced bone loss, through Y2 receptor‐mediated modulation of central and peripheral noradrenergic neurons. © 2014 American Society for Bone and Mineral Research.